PEDAGOGICAL CONTENT KNOWLEDGE MAHASISWA PENDIDIKAN FISIKA UNIVERSITAS JAMBI PADA PRAKTIK LAPANGAN PERSEKOLAHAN - M.Hidayat; Dani, Rahma; Lestari, Neneng (EduFisika: Jurnal Pendidikan Fisika, 2020)
This study aims to describe the ability of pedagogical content knowledge students of Physics Education Jambi University who take School Field Practices (SFP). This research was a survey research. The population of this research was 85 students who are taking SFP. The number of samples used was 20% of the population. Data were collected using a questionnaire. Data were analyzed descriptively. The results showed that the students' pedagogical content knowledge ability was in a good category. Aspects of pedagogical content knowledge consist of subject matter knowledge, instruction representation and strategies, instructional objective and context and knowledge of student understanding.